Community participation in the utilization of village fund for stunting prevention: Case study in two villages in Gianyar District - Prabasari, Made Ayu Diah; Lubis, Dinar Saurmauli; Sutiari, Ni Ketut (Universitas Udayana, 2021)
Background and purpose: The Indonesian government has set a target to reduce stunting prevalence from 27.7% in 2019 to 14% in 2024. There are 10 villages in Gianyar District have been selected as stunting loci since 2018, however, the percentages of the village fund utilized for health and nutrition were low. This research aims to identify the level of community participation in the utilization of village fund for stunting prevention in two stunting loci villages in Gianyar. Methods: This was a qualitative study using a multiple case study approach conducted in two stunting loci villages in Gianyar, Bali. Data collection was conducted from May to June 2020 through in-depth interview with 12 key informants. Thematic qualitative analysis was done using the ladder of participation concept with Arnsteinand political approach by Carpentier which involves several key concepts such as process, field, actor, decision making moment and power. Results: The level of community participation in the village fund utilization for stunting prevention was still in the of pseudo participation – Placation level. The majority of proposals or recommendation for stunting prevention program came from cadres of community health post, health care workers and the village assistants. Final decision making in the planning stage was largely depending on the village government. The community plays the role as program recipient. Several challenges for optimal utilization of village fund for stunting prevention were geographical condition, paternalistic leadership as well as the lack of understanding and capacity of key actors. Conclusion:The community participation in utilization of the village fund for stunting program in the two villages was in the vague participation level. The village government should provide more rooms to empower the community in order to increase their participation level.